Antifungal effect and action mechanism of antimicrobial peptide polybia‐CP. (18th December 2015) - Wang, Kairong; Jia, Fengjing; Dang, Wen; Zhao, Yanyan; Zhu, Ranran; Sun, Mengyang; Qiu, Shuai; An, Xiaoping; Ma, Zelin; Zhu, Yuanyuan; Yan, Jiexi; Kong, Ziqing; et al.
Abstract : The incidence of life‐threatening invasive fungal infections increased significantly in recent years. However, the antifungal therapeutic options are very limited. Antimicrobial peptides are a class of potential lead chemical for the development of novel antifungal agents. Antimicrobial peptide polybia‐CP was purified from the venom of the social wasp Polybia paulista . In this study, we synthesized polybia‐CP and determined its antifungal effects against a series of Candidian species. Our results showed that polybia‐CP has potent antifungal activity and fungicidal activity against the tested fungal cells with a proposed membrane‐active action mode. In addition, polybia‐CP could induce the increase of cellular reactive oxygen species production, which would attribute to its antifungal activity. In conclusion, the present study suggests that polybia‐CP has potential as an antifungal agent or may offer a new strategy for antifungal therapeutic option. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd. Abstract : In the present study, we synthesized cationic antimicrobial peptide polybia‐CP and determined its antifungal activity. Polybia‐CP could disturb the integrity of cell membrane of fungi cells and lead to the uptake of propidium iodide into cells. This suggest that the corruption of the integrity of the cell membrane, the cell content could leak out of the cell and result in the death of candida cells, which would be a proposed mechanism of polybia‐CP to exert its antifungal activity.